The challenge of public-private partnerships : learning from international experience - Hodge, Graeme A.; Greve, Carsten (Cheltenham, UK ; Northampton, Mass. : Edward Elgar Pub., 2005)
This book contains the challenges of public-private partnership as cooperative institutional arrangements between public and private sector actors-have now gained wide interest around the world.
Includes bibliographical references and index.
aug 30/05/13
Loans
Keywords: Public-private sector cooperation; Government-sponsored enterprises; Public contracts; Public works